ANALISIS YURIDIS USAHA PERIKANAN PASCA UNDANG-UNDANG NOMOR 11 TAHUN 2020 CIPTA KERJA - Shandra Mellany Aldalia; Endang Pandamdari (Reformasi Hukum Trisakti, 2021)
In order to create jobs and increase investment, the government simplified numbers of statutory regulations commonly called the Omnibus Law. From Omnibus Law, Law Number 11 of 2020 concerning Job Creation was born. It changed and deleted several articles in the law. One of them is Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries. The most dominant articles related to licensing simplification are integrated in UUCK. The main problems in this research are What are the factors led to the birth of UUCK which regulates Maritime Affairs and Fisheries and the similarities and differences in fishing business from Law Number 31 of 2004 Juncto Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries with UUCK. This research is a normative and analytical descriptive legal research by using secondary data and primary data to support secondary data. The data is analyzed qualitatively and the conclusions are drawn by using deductive methods. It can be concluded that UUCK amended that every fishing business activity must have Business Permit. This business license is made by taking the risk-based licensing process into account.